TRADITION AND MODERNITY: ORTHODOX INTERPRETATION OF QS. AL-FATIHAH IN THE STUDY QURAN - Riza, Zikri; Kusmana; Idris, Mhd. (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
Implying the identical meaning, the term orthodox Islam or traditional Islam is understood as the correct doctrine in accordance with official teachings. Both are symbols of the maintenance of old religious ways that originate from an authoritative entity that must be obeyed. Assuming to impose the same way, The Study Quran by Seyyed Hossein Nasr and his team also maintain the tradition of interpreting the Quran with unique characteristics of orthodoxy. The present work aims to explicate the orthodoxy of the tradition-based interpretation contained in the work of these traditionalist scholars by focusing on QS. al-Fatihah/1’s commentary in its seven verses. The modern orthodoxy approaches remain relevant to the first surah since its everyday performance articulates the traditionalism of religious practice. We conclude that the authorship of The Study Quran is an effort to preserve traditional methods of modern Quranic interpretation as reflected through the scriptural and community elements of Islamic orthodoxy. The Study Quran's orthodoxy is characterized by the interpretation based on discursive tradition which allows the development of existing discourse and thought. It contributes to the idea that modernity does not necessarily mean quitting old conducts inherited by the treasure of traditional ‘ulum al-Qur’an. Moreover, modern interpretation orthodoxy does not withdraw from the dynamics of thoughts in diversified religious groups of Islam.